STUDI MALAPRAKTEK PEMILU DI TEMPAT PEMUNGUTAN SUARA PADA PEMUNGUTAN DAN PENGHITUNGAN SUARA PEMILU SERENTAK TAHUN 2019 DI KABUPATEN BUTON - -, Awaludin (Bahasa Indonesia, 2019)
This study aims to determine the forms of Election malpractice that occur in the process of voting and counting at polling stations (TPS) in the implementation of simultaneous elections in 2019 in Buton District. Other than that, this study also aims to identify what factors influence the occurrence of Election Malappractice in Buton District, focus on the process of voting and counting at polling stations. The method used in this study is description research. Data sources in writing this thesis consist of primary data and secondary data. Primary data in the form of interviews and observations. Structured interviews were conducted with election organizers in Buton Regency in this case members of Bawaslu, KPU, PPK, PPS and KPPS. While observations in the voting and counting process are conducted in 2 (two) different polling stations, namely TPS 001 Bungi Village, and 004 TPS, Kombeli Village. Meanwhile, secondary data in the form of voter data, data on the results of voting and counting, recapitulation of the results of vote counting, letters, and regulations related to the voting and counting process. The data that has been obtained is then analyzed by reducing, presenting and drawing conclusions. The results of the study showed that there were malpractices in the election in the process of voting and counting at polling stations in the form of ghost voters, double voting, writing inaccurate C1 form, manipulation of vote acquisition of Election participants, lack of logistics, inaccurate voter data, voting that does not provide comfort for all groups of voters and the implementation of voting and counting in a certain degree it is not transparent and inaccurate. While the factors that influence the occurrence of malpractice are in the form of heavy workload, lack of competency of KPPS officers, changing regulations and no legal certainty, witnesses to the Election participants did not understand their duties and roles at the polling station, and a large amount of logistics.